Relationships between captive chimpanzee (Pan troglodytes) welfare and voluntary participation in behavioural studies - Neal Webb, Sarah J. (Appl Anim Behav Sci, 2019)
Voluntary participation in behavioural studies offers several scientific, management, and welfare benefits to non-human primates (NHPs). Aside from the scientific benefit of increased understanding of NHP cognition, sociality, and behaviour derived from noninvasive behavioural studies, participation itself has the potential to provide functional simulations of natural behaviours, enrichment opportunities, and increased control over the captive environment, all of which enhance welfare. Despite a developing consensus that voluntary participation offers these welfare enhancements, little research has empirically investigated the ways that participation in behavioural studies may affect welfare. In the current study, we investigated potential relationships between captive chimpanzee welfare and long-term, repeated voluntary participation in noninvasive behavioural studies. We collected behavioural data on 118 chimpanzees at the National Center for Chimpanzee Care (NCCC) in Bastrop, Texas, USA between 2016 and 2018 using 15-minute focal animal samples. Additionally, we collected information on 41 behavioural studies conducted between 2010 and 2018 with the NCCC chimpanzees that involved exposure to a stimulus or manipulation. The total number of behavioural studies in which chimpanzees had participated over the approximately eight-year period was then examined in relation to levels of behavioural diversity, abnormal behaviour, rough scratching, inactivity, and locomotion using a series of regression analyses that controlled for rearing status and age of the chimpanzee at the time of data collection. Analyses revealed significant, positive relationships between the total number of studies in which chimpanzees participated and 1) behavioural diversity scores, R(2)(adj) = .21, F(3,114) = 11.25, p < 0.001; and 2) rough scratching, R(2)(adj) = .11, F(3,114) = 6.01, p = 0.001. The positive relationship between behavioural diversity scores and the total number of studies in which chimpanzees participated seems unsurprising, although we cannot draw conclusions about the directionality of this relationship. The result that rough scratching and the total number of studies in which chimpanzees participated were positively correlated is unexpected. However, rough scratching made up less than 1% of all activity in the current study, and as such, this result may not be biologically meaningful. These findings suggest that participation in behavioural studies is not likely to be detrimental to chimpanzee well-being, and may even be beneficial. Data such as these, which empirically investigate existing recommendations can help inform decisions pertaining to the participation of chimpanzees in behavioural research.